(3GdHjJ GdeYehQs (3efGSc GdML hGdYeQI hBOGH GdRjGQI (B: (3eSLO GdQShd Udi Gddg Ydjg hSdes ((3GdbGgQIs (3gGj ajdes, 2001)
(3ajde JSLjdj Yf efGSc GdML hGdYeQI echf ef LRFjf jJfGhd efGSc GdML hGdYeQI HGdYQV hGdJMdjd hjDQN defGSc GdML efP Ndb BOe MJi bGe SjOfG EHQGgje hESeGYjd YdjgeG GdSdGe HQaY GdbhGYO ef GdHjJ Ke jJfGhd efGSc GdML cQcf ef CQcGf GdESdGe GdNeS (B.(3TQYg Gddg def GSJWGY Edjg SHjdkG hcjajI COGA efGSc GdML hadSaI gPg GdefGSc eY GdETGQI Edj MLI GdhOGY GdJj bGe HgG GdQShd Udi Gddg Ydjg hSde aj GdSfI GdYGTQI ef GdgLQI Ke BOGH RjGQI eSLO GdQShd hebUhQJg Udi Gddg Ydjg hSdes
(3JeJ GdeQGLYI aj EOGQIs
Keywords: (3EadGes -- (3OjfjIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs